2018
DOI: 10.1007/s12178-018-9471-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Management of Rotator Cuff Tears: a Primary Care Perspective

Abstract: In the primary care setting, rotator cuff pathology is commonly encountered. Information regarding the risks of oral medications for the management of the associated pain keeps mounting. Partial-thickness rotator cuff tears remain difficult to diagnose with a single imaging modality. Musculoskeletal education in medical schools and non-orthopaedic residency and fellowship training programs continues to be an area for additional improvement. In the primary care office, the initial evaluation of shoulder pain sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
0
10
0
2
Order By: Relevance
“…Edwards et al, 12 in their 2016 review of the literature, showed that conservative treatment can be effective in those with small (<1 cm) full-thickness tears, as well as older (>65 years) patients with chronic, full-thickness tears and associated muscle atrophy and fatty infiltration. Mathiasen and Hogrefe 13 suggest a course of conservative therapy for chronic tears in their primary care perspective paper as well. These studies highlight the effectiveness of nonoperative treatment for full-thickness rotator cuff tears.…”
Section: Discussionmentioning
confidence: 99%
“…Edwards et al, 12 in their 2016 review of the literature, showed that conservative treatment can be effective in those with small (<1 cm) full-thickness tears, as well as older (>65 years) patients with chronic, full-thickness tears and associated muscle atrophy and fatty infiltration. Mathiasen and Hogrefe 13 suggest a course of conservative therapy for chronic tears in their primary care perspective paper as well. These studies highlight the effectiveness of nonoperative treatment for full-thickness rotator cuff tears.…”
Section: Discussionmentioning
confidence: 99%
“…Higher age and a positive Neer test were found to be the most important predictors of rotator cuff tears [2]. Another study found combinations of certain aspects of the history and physical exam led to a greater diagnostic accuracy of rotator cuff tears [3]. Neither of these studies, however, used both ultrasound and MRI nor were components of the physical exam or history found to help guide clinicians in choosing one imaging modality over another.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently no widely agreed upon patient metrics which allow for accurate and timely supraspinatus tendinopathy diagnosis and efficient use of resources [2]. One study showed that a higher age and positive Neer test were important predictors of rotator cuff tear, although the sample size was small [3]. Another study showed certain aspects of the physical exam and history in combination led to the accurate detection of a rotator cuff tear, although only X-ray and ultrasound were used as the imaging modalities [4].…”
Section: Introductionmentioning
confidence: 99%
“…12 Pharmacological treatments, such as nonsteroidal anti-inflammatory drugs (NSAIDs), and nonpharmacological treatments, such as corticosteroid injections and physical therapy (PT), have been described in the management of rotator cuff tears, with the goal of reducing pain and physical disability and improving function. 4,17,28,30…”
mentioning
confidence: 99%